Stand structure and plant diversity characteristics of typical artificial forests after natural recovery in the hilly region of central Hainan - Wei, Jianxing; Chen, Haihui; Yu, Xuebiao; Guo, Zhaobin; Zhang, Xuefeng; Tian, Leyu; Nong, Shouqian (Frontiers in Plant Science, 2025)
IntroductionThe global expansion of artificial forests has highlighted the necessity of restoring their ecological service functions and understanding natural succession mechanisms in forest restoration ecology. However, comprehensive analyses of community assembly in tropical artificial forests following long-term natural recovery and their divergence from zonal vegetation remain insufficient.MethodsIn this study, the stand structure and plant diversity were investigated in three typical tropical artificial forests (Acacia mangium, Hevea brasiliensis, and Eucalyptus) after 20 years of natural recovery, alongside 33-year-old natural secondary forests, in the Fengmu Experimental Forest Farm, Hainan Province. The relationships between plant diversity and community structural factors in artificial forests were also examined.ResultsThe findings can be summarized as follows. (1) Acacia mangium forests exhibited superior natural regeneration, whereas the naturally regenerated trees in all plantations displayed significantly smaller mean diameter at breast height and height than those in the natural secondary forests. (2) Although the species diversity in certain forest layers of plantations approached that of natural secondary forests, notable differences persisted, and woody plants in plantations lacked the phylogenetic traits observed in natural secondary forests. (3) Redundancy analysis showed that the greater densities and canopy cover of planted trees inhibited arbor layer diversity but promoted phylogenetic dispersion. High tree density facilitated shrub layer establishment, whereas height growth in regenerated trees and shrubs inhibited shrub diversity through resource competition. Additionally, the increased diameter class variation in regenerated trees and taller shrub-herb layers reduced herb layer diversity due to resource limitations.DiscussionAfter 20 years of natural recovery, plantations have developed multi-aged, vertically stratified mixed stands. However, growth constraints on woody plants and limited biodiversity recovery persist. Structural optimization is crucial for enhancing niche differentiation and accelerating succession toward climax forest communities.